2010
DOI: 10.2174/157016210791330419
|View full text |Cite
|
Sign up to set email alerts
|

Both HIV-Infection and Long-Term Antiretroviral Therapy are Associated with Increased Common Carotid Intima-Media Thickness in HIV-Infected Adolescents and Young Adults

Abstract: HIV infection and longer duration of cART are associated with higher CCIMT in adolescents and young adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 40 publications
1
20
0
1
Order By: Relevance
“…56 The risk of CHD is also likely to be higher in patients with chronic inflammation. 57 Carotid artery intima-media thickness (cIMT), a surrogate marker of artherosclerosis, has been associated with vascular inflammation in HIV-positive patients; 58,59 and HIV-positive patients are at increased risk for progression of cIMT compared with sex-and age-matched controls. 50,60 However, others have not shown an increased cIMT in HIV-positive patients compared with HIV-negative controls.…”
Section: Hiv Infectionmentioning
confidence: 99%
“…56 The risk of CHD is also likely to be higher in patients with chronic inflammation. 57 Carotid artery intima-media thickness (cIMT), a surrogate marker of artherosclerosis, has been associated with vascular inflammation in HIV-positive patients; 58,59 and HIV-positive patients are at increased risk for progression of cIMT compared with sex-and age-matched controls. 50,60 However, others have not shown an increased cIMT in HIV-positive patients compared with HIV-negative controls.…”
Section: Hiv Infectionmentioning
confidence: 99%
“…CCA-IMT is a surrogate endpoint measure of atherosclerosis and has been shown to be increased in several studies on pediatric HIV. [5][6][7] Increased CCA-IMT has been associated with elevated high blood pressure and C-reactive protein, 7 insulin and glycosylated hemoglobin levels, 6 severe symptoms of HIV infection and use of protease inhibitors, 13 long-term exposure to HAART, [14][15][16] increased suprailiac skinfold, stavudine use, and low CD4+ T-lymphocyte count.…”
Section: Resultsmentioning
confidence: 99%
“…Among HIV-infected subjects, CCIMT was associated with the duration of exposure to a PI-based and NNRTI-based regimen plus single or double nucleoside reverse transcriptase inhibitors (11-20 years), but not with that of a NNRTI-based regimen (0-5 years), PI-based regimen (0-12 years), or NNRTI-and PI-based regimen (1-11 years). The authors concluded that HIV infection and long duration of ARV are risk factors for higher CCIMT in adolescents and young adults [40].…”
Section: Editorialmentioning
confidence: 98%